Study of blood flow patterns in a stenosed artery through the combined effect of body acceleration and generalized womersley solution - Mahesh C. Udupa; Sunanda Saha; Sekarapandian Natarajan (Scientific Reports)
Abstract Stenosis causes the narrowing of arteries due to plaque buildup, which impedes blood flow and affects flow dynamics. This work numerically analyzes flow fluctuations in stenosed arteries under realistic physiological conditions (resting and exercise) and external body acceleration. The artery is inclined at angle $$Θ$$ Θ , and blood rheology is modeled using a generalized power-law fluid. A modified two-dimensional SIMPLE pressure-correction-based numerical solver with orthogonal coordinate transformation simulates blood flow. A generalized Womersley solution is imposed at the inlet. We validate the solver and perform simulations to assess the influence of geometric and flow parameters, analyzing time-averaged and phase-averaged data. We investigate the correlation between hyperviscosity and physiological conditions, finding that exercise increases recirculation downstream of the stenosis. We also study the impact of transitioning between resting and exercise conditions, noting that the transition rate correlates with stenosis development, indicating potential complications.